Energy efficiency and economy-wide rebound: Realising a net gain to society? - Lisa Ryan; Karen Turner; Nina Campbell (University College Dublin, UCD School of Economics, 2017)
Economy-wide rebound in energy use is often presented as a necessary "evil" accompanying economic expansion triggered by energy efficiency improvements. We challenge this position in two, inter-related ways. First, we question the emphasis on potential technical energy savings and losses due to rebound in energy efficiency policy evaluation. This abstracts from the wider economic and societal impacts of energy efficiency improvements that are often positive and valuable to policy makers. Second, we propose that economic expansion and economy-wide rebound need not be highly correlated. We argue that energy efficiency actions targeted at improving the competitiveness of less energy-intensive means of providing services, such as heat and transport, may provide opportunities to boost economic activity while minimising rebound effects. This perspective involves a change in current policy and research thinking, particularly in terms of the type of substitution possibilities that we should focus on in enhancing energy efficiency, economic expansion and rebound relations.
Keywords: Q43; Q48; E2; 330; Energy policy; Energy economics; Economy-wide rebound; Energy efficiency